G445(P) 'being listened to': a retrospective analysis of the subjective value of psychotherapist-facilitated staff support sessions for paediatric junior doctors. (May 2019) - Daniels, RA; Hanson, C; Pallawela, J; Pedraz, A; Walker, L
Abstract : Aims: To evaluate the value to trainees of the staff support programme; To analyse feedback for themes for improvement. Methods: In a busy District General Hospital, monthly 1 hour sessions were included in the junior doctor teaching timetable where trainees would be able to discuss issues that affected them due to the psychological strains of the job. The sessions were instigated after the traumatic death of a patient, along with regular service pressures such as rota gaps, safeguarding cases and CAMHS cases. These sessions were optional, confidential within the room and had no consultant presence. The goal was to offer a safe, emotionally-reflective space to support trainee wellbeing. They were facilitated by 2 experienced psychoanalytic child psychotherapists who had been working in the department with patients, families and staff for many years. The direction of discussion was trainee-led and was based on a model of listening and reflecting. Participants were able to contribute as much or as little as they wanted and were able to leave at any time. Results: In the 5 months analysed, 53 trainees attended the sessions (mean 10.6 doctors/session). 36 doctors (68%) had previously attended support sessions, either at the same or other trusts. 53 (100%) of participants said they would recommend the sessions to others and would attend further sessions. Thematic evaluation of free-text feedback highlighted common benefits such as 'recognising shared experiences', 'learning from others' and 'encouraging team bonding'. A suggestion for improvement was to structure sessions either by topic or by trainee grade. Conclusions: Our results have shown that the feelings raised were universal and support previous findings elsewhere. The participants felt definite benefit from these sessions. The offer of a safe space to share feelings along with the recognition that individuals were not alone in how they felt, offered benefits to how well the team operated. More work needs to be done in looking at how this translates to clinical practice and how the programme can sustain these improvements as trainee cohorts change.